Foaming sound absorption material with high aperture ratio as well as preparation method and application of foaming sound absorption material

By using bio-based degradable polymers and supercritical carbon dioxide physical foaming methods, the foaming sound absorbing materials with high porosity is solved, and the problem of decomposition of existing sound absorbing materials in high-temperature processing is achieved, achieving the dual advantages of efficient sound absorbing performance and environmental protection.

CN119570099AActive Publication Date: 2025-03-07ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411860609.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing sound-absorbing materials may decompose during high-temperature processing, release harmful substances, and have complex preparation processes and high cost.

Method used

Bio-based degradable polymers such as polylactic acid, polyadipic acid/butylene terephthalate and polyhydroxy fatty acid esters are used as raw materials to prepare foamed sound-absorbing materials with high porosity through supercritical carbon dioxide physical foaming method.

Benefits of technology

It achieves efficient sound absorption performance, environmental protection, biodegradability, reduces carbon emissions, and simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570099A_ABST
    Figure CN119570099A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sound-absorbing materials, in particular to a foaming sound-absorbing material with a high aperture ratio structure and a preparation method and application thereof.The foaming sound-absorbing material comprises one or more of polylactic acid, poly (adipic acid) / butylene terephthalate and polyhydroxyalkanoate, the density of the foaming sound-absorbing material is 0.04-0.08 g / cm < 3 >, and the porosity of the foaming sound-absorbing material is 20-30%. The aperture ratio of the foaming sound absorption material is higher than 60%. According to the invention, the polymer foaming sound absorption material with high aperture ratio can be prepared without adding other fillers and assistants, the prepared foaming sound absorption material has the characteristics of high aperture ratio, small density and the like, and the foaming sound absorption material can realize efficient absorption of sound waves in a thickness range of 10 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sound absorbing materials, and in particular to a foamed sound absorbing material with a high open porosity, a preparation method thereof and application thereof. Background Art

[0002] Existing sound-absorbing materials are mainly composed of two categories: resonant sound-absorbing materials and foamed sound-absorbing materials. Foamed sound-absorbing materials have great development potential due to their low cost, mature processing technology, light weight, and wide application range. When sound waves hit porous materials, sound energy will be reflected, absorbed, and transmitted. After the sound waves enter the foamed material, they cause the air in the pore cavity to vibrate. The air vibration is blocked by the complex and tortuous pore walls, and the friction and viscosity between the air vibration and the pore walls cause part of the sound energy to be converted into heat energy dissipation, resulting in energy loss. The thickness of the material also has a great influence on the sound absorption performance. The thicker the material, the higher the cost of its application.

[0003] In the prior art, for example, patent CN115966192A provides a method for improving the performance of a cavity resonance sound-absorbing structure based on lattice reflection. This method is based on the basic principle that the local resonance of phononic crystals produces a band gap. By increasing the lattice outer frame, changing the ratio of the lattice outer frame volume to the cavity resonance sound-absorbing structure volume, adjusting the structural geometric parameters of the lattice outer frame, a double resonance system is generated, and then a sound-absorbing lattice with double sound absorption peaks under a certain working frequency range is obtained, thereby improving the sound absorption performance of the original cavity resonance sound-absorbing structure. However, the process and operation of establishing the lattice outer frame are complicated, and the requirements for each parameter are strict. For example, CN118725238A provides a polyurethane flexible foaming sound-absorbing material, a sandwich structure sound-absorbing material and a preparation method. The foaming sound-absorbing material prepared by this method has good waterproofness and pressure resistance and has lower density and thickness. However, this method uses polytetrahydrofuran as a raw material, which has low toxicity, and during high-temperature processing, polytetrahydrofuran may decompose and release tetrahydrofuran monomers or other low molecular weight compounds, which may irritate the respiratory tract. Summary of the invention

[0004] The present invention is made to solve the above problems, and aims to provide a foamed sound-absorbing material with a high open porosity, a preparation method and application thereof.

[0005] The first aspect of the present invention provides a foamed sound-absorbing material with a high open porosity, characterized in that: The raw materials of the foamed sound-absorbing material include one or more of polylactic acid, polybutylene adipate / terephthalate, and polyhydroxyalkanoate. The density of the foamed sound-absorbing material is 0.04-0.08 g / cm 3 , the open porosity of the foamed sound-absorbing material is higher than 60%.

[0006] The present invention uses bio-based degradable polymers such as polylactic acid, polybutylene adipate / terephthalate and polyhydroxyalkanoate as raw materials to prepare foamed sound-absorbing materials, which have the advantages of environmental protection, biodegradability, reduced carbon emissions, excellent sound absorption performance, friendly processing, good mechanical properties and sustainability. The present invention can use a supercritical carbon dioxide physical foaming method without adding other fillers and additives to prepare a polymer foamed sound-absorbing material with a high open porosity. The foamed sound-absorbing material has a simple preparation process, is environmentally friendly and non-toxic, and the prepared foamed sound-absorbing material has the characteristics of high open porosity and low density. Due to the high open porosity structure of the foamed sound-absorbing material, sound waves can more effectively enter the interior of the foamed sound-absorbing material, promote the conversion and dissipation of sound energy, thereby improving the overall sound absorption coefficient, so the foamed sound-absorbing material can achieve efficient absorption of sound waves within a thickness range of 10 mm.

[0007] The present invention achieves superior acoustic performance by controlling the foaming conditions to adjust and optimize the pore size and open porosity of the foaming material, which not only improves the sound absorption effect, but also brings advantages in lightweight and cost-effectiveness. It has broad application prospects and can meet the needs of various acoustic applications, such as architectural acoustics, automotive interiors, and electronic equipment.

[0008] The second aspect of the present invention provides a method for preparing a foamed sound-absorbing material with a high open porosity as described in the first aspect, characterized in that it comprises the following steps: (1) drying the raw material and then tableting it to obtain a tablet sample; (2) Using a supercritical carbon dioxide physical foaming method, the pressed sample is placed in a foaming container for immersion treatment and then foamed, and the pressure is released to obtain the foamed sound absorbing material, wherein the immersion temperature is higher than the foaming temperature.

[0009] In the embodiments, since the presence of moisture may affect the processing properties of the raw materials and the quality of the final product, such as generating bubbles during processing or affecting the melting behavior of the material, the moisture in the raw materials is removed by drying the raw materials.

[0010] Furthermore, the dried raw material is subjected to tabletting treatment to be pressed into uniform sheets, which helps to improve the density of the raw material and provide a better base material for the foaming process, so as to facilitate the subsequent foaming treatment.

[0011] Furthermore, a supercritical carbon dioxide physical foaming method is adopted to control the pressure and temperature in the foaming container to be higher than the critical point of carbon dioxide, and an intermittent foaming method is adopted to divide the foaming process into two steps of high-temperature immersion and low-temperature foaming, and the immersion temperature is controlled to be higher than the foaming temperature. The high-temperature immersion improves the fluidity of the polymer melt during the immersion process, accelerates the diffusion rate of carbon dioxide, makes the carbon dioxide evenly distributed in the melt, increases the solubility of carbon dioxide in the polymer melt, utilizes low-temperature foaming to better control the foaming speed, and forms more bubble nuclei during the foaming process to form a more uniform foam structure, thereby generating more bubbles during the pressure-reducing foaming and improving the foaming efficiency, thereby shortening the immersion time, improving production efficiency, controlling the foaming process and the foam structure, and improving the mechanical properties of the foamed sound-absorbing material, such as compressive strength and elastic modulus.

[0012] In some embodiments, in step (1), the drying temperature is 40-60° C. and the drying time is 6-12 hours.

[0013] In some embodiments, in step (1), a flat-plate vulcanizing machine is used for tableting.

[0014] In some embodiments, in step (1), the tableting conditions are: increasing pressure by 3-5 MPa for 1-5 min; maintaining pressure by 8-10 MPa for 2-5 min.

[0015] In the embodiment, the pressure is increased by 3-5 MPa to quickly reach the pressing pressure, and the pressure is maintained at 8-10 MPa to ensure that the structure of the tablet sample is uniform and free of defects.

[0016] In some embodiments, in step (2), the soaking temperature is 130-160°C.

[0017] In some embodiments, in step (2), the foaming temperature is 100-120°C.

[0018] In some embodiments, the step (2) specifically includes: placing the pressed sample in a foaming container at a constant pressure of 11 to 16 MPa, soaking it at the soaking temperature for 30 to 180 min, adjusting it to the foaming temperature, keeping it warm for 15 to 180 min to foam, and releasing the pressure after the foaming is completed to obtain the foamed sound-absorbing material.

[0019] In the embodiment, the tablet sample is placed in a foaming kettle, and the gas in the tablet sample is dissolved under a constant pressure of 11-16 MPa to prepare for the foaming process, and the temperature of the foaming kettle is increased to 130-160°C and soaked at this temperature for 30-180 minutes to melt the tablet sample and increase the solubility of the gas in the tablet sample, thereby forming bubbles in the subsequent pressure release process.

[0020] Furthermore, the temperature of the foaming kettle is lowered to 100-120°C and kept warm for 15-180 min in order to control the melt viscosity of the tablet sample so that it can stably form a bubble structure when the pressure is released. Furthermore, the pressure is released after the insulation is completed, and the pressure is released instantly. This rapid pressure release causes the gas dissolved in the melt of the tablet sample to expand rapidly and form bubbles, thereby obtaining the foamed sound-absorbing material.

[0021] The third aspect of the present invention provides an application of a foamed sound-absorbing material with a high open porosity, characterized in that the foamed sound-absorbing material described in the first aspect or the foamed sound-absorbing material prepared by the preparation method described in the second aspect is used for noise prevention and control.

[0022] By implementing the above technical solution, the present invention has the following beneficial effects: The present invention uses bio-based degradable polymers such as polylactic acid, polybutylene adipate / terephthalate and polyhydroxyalkanoate as raw materials to prepare foamed sound-absorbing materials, which have the advantages of environmental protection, biodegradability, reduced carbon emissions, excellent sound absorption performance, friendly processing, good mechanical properties and sustainability. The present invention can prepare polymer foamed sound-absorbing materials with high open porosity without adding other fillers and additives. The foamed sound-absorbing material has a simple preparation process, is environmentally friendly and non-toxic, and the prepared foamed sound-absorbing material has the characteristics of high open porosity and low density. Due to the high open porosity structure of the foamed sound-absorbing material, sound waves can more effectively enter the interior of the foamed sound-absorbing material, promote the conversion and dissipation of sound energy, thereby improving the overall sound absorption coefficient. Therefore, the foamed sound-absorbing material can achieve efficient absorption of sound waves within a thickness range of 10 mm.

[0023] The present invention achieves superior acoustic performance by controlling the foaming conditions to adjust and optimize the pore size and open porosity of the foaming material, which not only improves the sound absorption effect, but also brings advantages in lightweight and cost-effectiveness. It has broad application prospects and can meet the needs of various acoustic applications, such as architectural acoustics, automotive interiors, and electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Electron microscope images of polymer foam materials of Example 1 (left) and Example 4 (right); Figure 2 The pore size of the high-opening-porosity foam material of Example 4; Figure 3 Sound absorption test curves of the foamed sound absorbing materials prepared in various embodiments; Figure 4 Flow chart for preparation of foamed sound-absorbing materials. DETAILED DESCRIPTION

[0025] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.

[0026] Example 1 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 140 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and it was soaked at this temperature and pressure for 60 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0027] Example 2 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 140 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and it was soaked at this temperature and pressure for 90 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0028] Example 3 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 140 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and it was soaked at this temperature and pressure for 120 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0029] Example 4 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 147 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and it was soaked at this temperature and pressure for 60 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0030] Example 5 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 147 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and it was soaked at this temperature and pressure for 90 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0031] Example 6 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 147 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and the mixture was soaked at this temperature and pressure for 120 min. Then, the temperature of the foaming kettle was lowered to 100 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0032] Example 7 First, pure PLA powder was placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw material; the dried polylactic acid raw material was pressed into tablets using a flat vulcanizer; the conditions were pressurization of 4 MPa for 1 min; pressure maintenance of 10 MPa for 2 min; polylactic acid tablet samples were obtained; supercritical carbon dioxide foaming was used for intermittent foaming. First, when the temperature of the foaming kettle was raised to 147 °C, the obtained polylactic acid strips were placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa, and the samples were soaked at this temperature and pressure for 120 min. Then, the temperature of the foaming kettle was lowered to 120 °C and kept warm for 30 min. After the insulation was completed, the pressure was released, and the pressure was released instantly to obtain a polymer foaming sample.

[0033] Example 8 First, pure PBAT and PLA pure materials were placed in an oven at 40 °C and dried for 8 hours to dry the moisture in the raw materials. PBAT and PLA were melt-blended at a weight ratio of 4:6 using a Haake torque rheometer to obtain a PBAT / PLA composite material; the PBAT / PLA composite material was tableted using a flat vulcanizer; the conditions were pressurized at 4 MPa for 1 min; maintained at 10 MPa for 2 min; a polylactic acid tablet sample was obtained; a supercritical carbon dioxide foaming constant temperature foaming method was used, and when the temperature of the foaming kettle was raised to 70 °C, the obtained PBAT / PLA composite material specimen was placed in the foaming kettle, and carbon dioxide was transported into the foaming kettle by an air compressor. The pressure in the foaming kettle was 13.8 MPa. After soaking at this temperature and pressure for 120 min, the pressure was released, and the pressure was instantly released to obtain a polymer foaming sample.

[0034] Performance Testing Porosity test: Vacuum density tester UPYC 1200e Quantachrome Instruments Density test: solid-liquid dual-purpose density meter JHY-S300 Jinheyuan Table 1 Opening rate and density test data table in the embodiment Opening rate <![CDATA[Density (g / cm 3 )]]> Example 1 63.10% 0.070 Example 2 60.00% 0.058 Example 3 61.09% 0.045 Example 4 61.87% 0.055 Example 5 69.31% 0.045 Example 6 70.87% 0.043 Example 7 63.23% 0.049 Example 8 60.02% 0.103 According to Table 1, compared with Examples 1 to 8, in Example 8, since a constant temperature foaming method is adopted, the immersion temperature and the foaming temperature are consistent, so the density of the foamed material obtained is larger.

[0035] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A foamed sound-absorbing material with a high open porosity, characterized in that: The raw materials of the foamed sound-absorbing material include one or more of polylactic acid, polybutylene adipate / terephthalate, and polyhydroxyalkanoate. The density of the foamed sound-absorbing material is 0.04-0.08 g / cm 3 , the open porosity of the foamed sound-absorbing material is higher than 60%.

2. A method for preparing a foamed sound-absorbing material with a high open porosity as claimed in claim 1, characterized in that: The following steps are involved: (1) drying the raw material and then tableting it to obtain a tablet sample; (2) Using a supercritical carbon dioxide physical foaming method, the pressed sample is placed in a foaming container for immersion treatment and then foamed, and the pressure is released to obtain the foamed sound absorbing material, wherein the immersion temperature is higher than the foaming temperature.

3. The preparation method according to claim 2, characterized in that: In the step (1), the drying temperature is 40-60° C. and the drying time is 6-12 h.

4. The preparation method according to claim 2, characterized in that: In the step (1), a flat plate vulcanizing machine is used for tableting.

5. The preparation method according to claim 4, characterized in that: In the step (1), the tableting conditions are: increasing the pressure by 3-5 MPa for 1-5 min; maintaining the pressure by 8-10 MPa for 2-5 min.

6. The preparation method according to claim 2, characterized in that: In the step (2), the soaking temperature is 130-160°C.

7. The preparation method according to claim 6, characterized in that: In the step (2), the foaming temperature is 100-120°C.

8. The preparation method according to claim 7, characterized in that: The step (2) specifically comprises: placing the pressed sample in a foaming container and soaking it at the soaking temperature for 30 to 180 minutes at a constant pressure of 11 to 16 MPa, adjusting the temperature to the foaming temperature, and keeping the temperature for 15 to 180 minutes to foam, and releasing the pressure after the foaming is completed to obtain the foamed sound absorbing material.

9. Application of a foamed sound-absorbing material with a high open porosity, characterized in that: The foamed sound-absorbing material according to claim 1 or the foamed sound-absorbing material prepared by the preparation method according to claims 2 to 8 is used for noise prevention and control.

Citation Information

Patent Citations

  • Polylactic acid foamed material and preparation method thereof

    CN102675842A

  • PLA / PBAT / Talc composite foaming oil absorption material with high foaming ratio and preparation method thereof

    CN112961395A

  • Preparation method of PLA (polylactic acid) alloy and foamed sheet

    CN115058104A

  • Polymer porous material with gradient change of aperture and preparation method thereof

    CN117264266A

  • Full-degradable polylactic acid foaming material and preparation method thereof

    CN117430859A

Cited By

  • Foaming processing technology of low-carbon type carbon dioxide-based polyether polyol sponge

    CN121471467A

  • A foaming process for low-carbon carbon dioxide-based polyether polyol sponges

    CN121471467B